Lithium cobalt oxide ceramic target material as well as preparation method and application thereof

Through grouting molding and atmospheric sintering processes, the problem of small size of lithium cobalt oxide ceramic targets in the prior art is solved, and high-efficiency and low-cost preparation of large-size ceramic targets is achieved, with good density and uniformity.

CN119874345AActive Publication Date: 2025-04-25KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510141523.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-25
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The lithium cobalt oxide ceramic target prepared in the prior art is small in size, and it is difficult to produce large-size lithium cobalt oxide ceramic targets with good uniformity and high density at low cost and efficiently.

Method used

Grouting molding and atmospheric sintering processes are adopted to prepare regular-shaped lithium cobalt oxide ceramic targets through grouting molding using the water absorption of gypsum molds, and the production process and cost are reduced through atmospheric sintering.

Benefits of technology

The density and uniformity of the preparation of large-size lithium cobalt oxide ceramic targets is achieved, and the production cost is reduced. It has the advantages of simplicity and efficiency, low cost, short forming cycle and easy batching.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005265018020000101
    Figure BDA0005265018020000101
  • Figure BDA0005265018020000111
    Figure BDA0005265018020000111
Patent Text Reader

Abstract

The invention relates to a lithium cobalt oxide ceramic target material and a preparation method and application thereof, and the preparation method comprises the following steps: (1) mixing a binder, a dispersant, a solvent and lithium cobalt oxide to obtain lithium cobalt oxide slurry; (2) sequentially carrying out defoaming, slip casting and drying on the lithium cobalt oxide slurry to obtain a lithium cobalt oxide green body; and (3) sequentially performing degreasing and normal-pressure sintering on the lithium cobalt oxide green body to obtain the lithium cobalt oxide ceramic target material. According to the preparation method, slip casting and normal-pressure sintering processes are adopted, the lithium cobalt oxide ceramic target material which is regular in shape, high in density and large in size can be prepared by slip casting and utilizing the water absorption of a plaster mold, and normal-pressure sintering is adopted, so that the production cost is reduced while the production procedures are reduced; the method has the advantages of simplicity, high efficiency, low cost, short forming period and easiness in batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium cobalt oxide materials and relates to a lithium cobalt oxide ceramic target material and a preparation method and application thereof. Background Art

[0002] The emergence of batteries has reduced people's dependence on non-renewable resources. With the rapid development of the electronics industry, electronic products are moving towards miniaturization, lightness, and portability, which puts forward new requirements for batteries. Lithium-ion solid-state batteries with greater energy density, longer cycle life, and higher operating voltage have attracted great attention. Compared with liquid lithium-ion batteries, all-solid-state batteries have higher safety, greater energy density, and a wider range of operating temperatures, and have now become the latest field of lithium-ion battery development.

[0003] The earliest positive electrode material of thin film battery is TiS 2 With the successful development of high-performance solid electrolyte LiPON, lithium cobalt oxide has also attracted extensive research as the positive electrode material of LiPON solid-state thin-film batteries. Lithium cobalt oxide not only has high voltage, high specific energy density and good cycle performance, but also has a simple process preparation process. It is currently the mainstream positive electrode material for lithium-ion batteries. With the development of thin-film solid-state batteries, higher requirements are also put forward for lithium cobalt oxide targets, which are positive electrode materials of magnetron sputtering all-solid-state thin-film batteries.

[0004] Slurry injection molding refers to the method of selecting appropriate additives to evenly suspend the powdered raw materials in the solution to form a fluid slurry, then pouring it into a water-absorbent plaster mold to absorb the water, and molding it according to the shape of the mold to obtain a green body with a certain strength. This method is often used to manufacture large-sized and complex-shaped ceramic targets, and this method has the advantages of regular green body shape, easy batch replication, short molding cycle, and low cost.

[0005] The lithium cobalt oxide ceramic target prepared in the prior art is relatively small in size. Therefore, how to prepare a large-sized lithium cobalt oxide ceramic target with good uniformity and high density at low cost and high efficiency has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a lithium cobalt oxide ceramic target material and a preparation method and application thereof. The present invention adopts slip injection molding and normal pressure sintering processes. Through slip injection molding, the water absorption of the gypsum mold is utilized to prepare a lithium cobalt oxide ceramic target material with regular shape, high density and large size. Normal pressure sintering is adopted to reduce the production process and reduce the production cost. The present invention has the advantages of simplicity, high efficiency, low cost, short molding cycle and easy mass production.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a lithium cobalt oxide ceramic target, the preparation method comprising the following steps: (1) mixing a binder, a dispersant, a solvent and lithium cobalt oxide to obtain a lithium cobalt oxide slurry; (2) sequentially degassing, injection molding and drying the lithium cobalt oxide slurry to obtain a lithium cobalt oxide green body; (3) sequentially degreasing and sintering the lithium cobalt oxide green body at normal pressure to obtain the lithium cobalt oxide ceramic target.

[0009] The present invention adopts slip injection molding and normal pressure sintering technology. Through slip injection molding, the water absorption of the gypsum mold is utilized to prepare a lithium cobalt oxide ceramic target material with regular shape, high density and large size. Normal pressure sintering is adopted to reduce the production process and the production cost at the same time. The invention has the advantages of being simple and efficient, low cost, short molding cycle and easy to mass produce.

[0010] Preferably, the binder in step (1) comprises polyvinyl alcohol.

[0011] Preferably, the amount of the binder is 2wt% to 5wt% of the total amount of the binder, dispersant and lithium cobalt oxide, for example, it can be 2wt%, 2.5wt%, 3wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] Preferably, the dispersant includes any one of polyacrylic acid, polyacrylamide, sodium hexametaphosphate or sodium acrylate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of polyacrylic acid and polyacrylamide, a combination of sodium hexametaphosphate and sodium acrylate, or a combination of polyacrylamide, sodium hexametaphosphate and sodium acrylate.

[0013] Preferably, the amount of the dispersant used accounts for 0.5wt% to 3wt% of the total amount of the binder, dispersant and lithium cobalt oxide, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the solvent comprises deionized water.

[0015] Preferably, the mixing in step (1) includes three-stage mixing.

[0016] Preferably, the one-stage mixing includes: a one-stage mixing of a solvent and a dispersant to obtain a one-stage mixed material.

[0017] Preferably, the mixing time is 0.5 h to 3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the two-stage mixing comprises: mixing the first-stage mixture and lithium cobalt oxide powder in two stages to obtain the second-stage mixture.

[0019] Preferably, the time of the second-stage mixing is 12 h to 24 h, for example, 12 h, 16 h, 18 h, 20 h, 22 h or 24 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the three-stage mixing includes: three-stage mixing of the second-stage mixture and a binder to obtain a mixed lithium cobalt oxide slurry.

[0021] Preferably, the three-stage mixing time is 12 h to 24 h, for example, 12 h, 16 h, 18 h, 20 h, 22 h or 24 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the degassing in step (2) comprises vacuum degassing.

[0023] Preferably, the vacuum degree of the vacuum degassing is -0.98Mpa to -0.90Mpa, for example, it can be -0.98Mpa, -0.96Mpa, -0.95Mpa, -0.94Mpa, -0.92Mpa or -0.90Mpa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the degassing device comprises a degassing tank.

[0025] Preferably, after the vacuum degassing and before the grouting molding, gas is filled into the degassing pot for pressurization.

[0026] Preferably, the gas comprises nitrogen and / or air.

[0027] Preferably, the pressurized pressure is 0.1 MPa to 1 MPa, for example, 0.1 MPa, 0.2 MPa, 0.4 MPa, 0.5 MPa, 0.7 MPa or 1 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the size of the gypsum mold for grouting molding in step (2) is length (40cm-60cm) × width (70cm-90cm) × thickness (10cm-30cm), for example, it can be length 40cm × width 70cm × thickness 10cm, length 50cm × width 80cm × thickness 20cm, length 40cm × width 90cm × thickness 30cm, length 60cm × width 70cm × thickness 30cm, length 60cm × width 90cm × thickness 10cm or length 60cm × width 90cm × thickness 30cm, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0029] Preferably, after the grouting molding and before drying, pressure maintenance is performed.

[0030] Preferably, the holding pressure is 0.1 MPa to 1 MPa, for example, 0.1 MPa, 0.2 MPa, 0.4 MPa, 0.5 MPa, 0.7 MPa or 1 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the pressure holding time is 3 h to 12 h, for example, 3 h, 6 h, 9 h, 10 h, 11 h or 12 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] The present invention can further improve the integrity and uniformity of the lithium cobalt oxide ceramic target by further regulating the pressure and time of the pressure holding. Within the preferred range of the pressure holding pressure and time, the prepared lithium cobalt oxide ceramic target has a complete green body, fully utilizes the raw materials, and facilitates the smooth progress of the subsequent drying step.

[0033] Preferably, the drying insulation temperature in step (2) is 40°C to 50°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the drying insulation time in step (2) is 20 h to 48 h, for example, 20 h, 24 h, 30 h, 35 h, 40 h or 48 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the drying device comprises a constant temperature and humidity chamber.

[0036] Preferably, the degreasing holding temperature in step (3) is 500°C to 600°C, for example, it can be 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the degreasing holding time in step (3) is 1 h to 5 h, for example, 1 h, 2 h, 3 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the degreasing device comprises a lifting furnace.

[0039] Preferably, the holding temperature of the atmospheric pressure sintering in step (3) is 950°C to 1000°C, for example, it can be 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the holding time of the atmospheric pressure sintering is 1 h to 5 h, for example, 1 h, 2 h, 3 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0041] The present invention can further improve the density of the lithium cobalt oxide ceramic target by further regulating the holding temperature and holding time of pressureless sintering. Within the preferred range of pressureless sintering holding temperature and holding time, the prepared lithium cobalt oxide ceramic target has a further improved density.

[0042] Preferably, the atmosphere of the normal pressure sintering is an oxygen-containing atmosphere.

[0043] Preferably, the oxygen-containing atmosphere comprises air and / or oxygen.

[0044] Preferably, the pressureless sintering device comprises a pressureless sintering furnace.

[0045] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0046] (1) adding a solvent and a dispersant, and mixing for 0.5 h to 3 h in the first stage; then adding lithium cobalt oxide powder, and mixing for 12 h to 24 h in the second stage; and finally adding a binder, and mixing for 12 h to 24 h in the third stage to obtain lithium cobalt oxide slurry.

[0047] (2) Pour the lithium cobalt oxide slurry into a degassing tank for vacuum degassing. After the degassing is completed, fill the degassing tank with gas for pressurization. The pressurization pressure is 0.1MPa~1MPa. The discharge port is connected to the gypsum mold. The lithium cobalt oxide slurry is automatically filled into the gypsum mold. After the filling is completed, the pressure is maintained at 0.1MPa~1MPa for 3h~12h, and the mold is removed and placed in a constant temperature and humidity box at 40℃~50℃ for drying for 20h~48h to obtain a lithium cobalt oxide green body.

[0048] (3) placing the lithium cobalt oxide green body into a lifting furnace for degreasing at a temperature of 500° C. to 600° C. for a degreasing time of 1 h to 5 h to obtain a degreased lithium cobalt oxide green body.

[0049] (4) placing the degreased lithium cobalt oxide green body into a pressureless sintering furnace for pressureless sintering at a temperature of 950° C. to 1000° C. for a holding time of 1 h to 5 h to obtain the lithium cobalt oxide ceramic target.

[0050] In a second aspect, the present invention provides a lithium cobalt oxide ceramic target material, which is prepared by the preparation method described in the first aspect.

[0051] Preferably, the size of the lithium cobalt oxide ceramic target is length (40cm~60cm)×width (70cm~90cm)×thickness (8cm~28cm), for example, it can be length 40cm×width 70cm×thickness 8cm, length 50cm×width 80cm×thickness 20cm, length 40cm×width 90cm×thickness 28cm, length 60cm×width 70cm×thickness 28cm, length 60cm×width 90cm×thickness 8cm or length 60cm×width 90cm×thickness 28cm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0052] In a third aspect, the present invention provides an application of the lithium cobalt oxide ceramic target material as described in the second aspect, wherein the lithium cobalt oxide target material is applied to the positive electrode of a solid-state thin-film battery.

[0053] Compared with the prior art, the present invention has at least the following beneficial effects:

[0054] The present invention adopts slip injection molding and normal pressure sintering processes. Through slip injection molding, the water absorption of the gypsum mold is utilized to prepare a lithium cobalt oxide ceramic target material with regular shape, high density and large size. Normal pressure sintering is adopted to reduce the production process and reduce the production cost. The invention has the advantages of being simple and efficient, low cost, short molding cycle and easy to mass produce. DETAILED DESCRIPTION

[0055] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a method for preparing a lithium cobalt oxide ceramic target, the preparation method comprising the following steps:

[0058] (1) Add 2 parts of polyacrylic acid and 200 parts of water into a powder mixing barrel and mix for 2 hours in the first stage; then add 95 parts of lithium cobalt oxide powder and mix for 12 hours in the second stage; finally add 3 parts of polyvinyl alcohol solution as a solute and mix for 12 hours in the third stage to obtain lithium cobalt oxide slurry;

[0059] (2) Pour the lithium cobalt oxide slurry into a degassing tank and perform vacuum degassing at a vacuum degree of -0.95 MPa. After the degassing is completed, fill the degassing tank with nitrogen for pressurization at a pressure of 0.5 MPa. The discharge port is connected to a plaster mold. The size of the plaster mold is 50 cm long × 80 cm wide × 20 cm thick. The lithium cobalt oxide slurry is automatically filled into the plaster mold. After the filling is completed, the pressure is maintained at 0.5 MPa for 9 hours, and the mold is removed and placed in a constant temperature and humidity chamber at 45° C. for drying for 36 hours to obtain a lithium cobalt oxide green body;

[0060] (3) placing the lithium cobalt oxide green body into a lifting furnace for degreasing at a temperature of 550° C. for a degreasing time of 3 h to obtain a degreased lithium cobalt oxide green body;

[0061] (4) The degreased lithium cobalt oxide green body is placed in a pressureless sintering furnace for pressureless sintering. The pressureless sintering temperature is 980° C. and the pressureless sintering holding time is 3 h to obtain the lithium cobalt oxide ceramic target.

[0062] The dimensions of the lithium cobalt oxide ceramic target prepared in this embodiment are 50 cm long×80 cm wide×18 cm thick.

[0063] Example 2

[0064] This embodiment provides a method for preparing a lithium cobalt oxide ceramic target, the preparation method comprising the following steps:

[0065] (1) adding 0.5 parts of sodium polyacrylate and 200 parts of water to the mixed powder, and mixing for 0.5 hours in the first stage; then adding 97.5 parts of lithium cobalt oxide powder, and mixing for 12 hours in the second stage; adding 2 parts of polyvinyl alcohol solution as the solute, and mixing for 12 hours in the third stage to obtain a mixed liquid slurry;

[0066] (2) Pour the lithium cobalt oxide slurry into a degassing pot and perform vacuum degassing at a vacuum degree of -0.90 MPa. After the degassing is completed, fill the degassing pot with nitrogen for pressurization at a pressure of 0.1 MPa. The discharge port is connected to a gypsum mold. The size of the gypsum mold is 40 cm long × 70 cm wide × 10 cm thick. The lithium cobalt oxide slurry is automatically filled into the gypsum mold. After the filling is completed, the pressure is maintained at 0.1 MPa for 12 hours, and the mold is removed and placed in a constant temperature and humidity box at 50° C. for drying for 20 hours to obtain a lithium cobalt oxide green body;

[0067] (3) placing the lithium cobalt oxide green body into a lifting furnace for degreasing at a temperature of 600° C. for a degreasing time of 1 h to obtain a degreased lithium cobalt oxide green body;

[0068] (4) placing the degreased lithium cobalt oxide green body into a pressureless sintering furnace for pressureless sintering at a temperature of 1000° C. and a pressureless sintering holding time of 1 h to obtain the lithium cobalt oxide ceramic target.

[0069] The dimensions of the lithium cobalt oxide ceramic target prepared in this embodiment are 40 cm in length×70 cm in width×9 cm in thickness.

[0070] Example 3

[0071] This embodiment provides a method for preparing a lithium cobalt oxide ceramic target, the preparation method comprising the following steps:

[0072] (1) adding 3 parts of polyacrylamide and 200 parts of water to the mixed powder, mixing for 3 hours in the first stage; then adding 92 parts of lithium cobalt oxide powder, mixing for 24 hours in the second stage; adding 5 parts of polyvinyl alcohol solution as a solute, mixing for 24 hours in the third stage, and obtaining a mixed liquid slurry;

[0073] (2) Pour the lithium cobalt oxide slurry into a degassing machine and perform vacuum degassing at a vacuum degree of -0.98 MPa. After the degassing is completed, nitrogen is filled into the degassing tank for pressurization. The pressurization pressure is 1 MPa. The discharge port is connected to a gypsum mold. The size of the gypsum mold is 60 cm long × 90 cm wide × 30 cm thick. The lithium cobalt oxide slurry is automatically filled into the gypsum mold. After the filling is completed, the pressure is maintained at 1 MPa for 3 hours, and the mold is removed and placed in a constant temperature and humidity chamber at 40° C. for drying for 48 hours to obtain a lithium cobalt oxide green body;

[0074] (3) placing the lithium cobalt oxide green body into a lifting furnace for degreasing at a temperature of 500° C. for a degreasing time of 5 h to obtain a degreased lithium cobalt oxide green body;

[0075] (4) The degreased lithium cobalt oxide green body is placed in a pressureless sintering furnace for pressureless sintering. The pressureless sintering temperature is 950° C. and the pressureless sintering holding time is 5 h to obtain the lithium cobalt oxide ceramic target.

[0076] The dimensions of the lithium cobalt oxide ceramic target prepared in this embodiment are 60 cm long×90 cm wide×27 cm thick.

[0077] Example 4

[0078] The only difference between this embodiment and embodiment 1 is that, except that the pressure of the pressure-maintaining step (2) is 0.08 MPa, the rest is the same as embodiment 1.

[0079] Example 5

[0080] The only difference between this embodiment and embodiment 1 is that, except that the pressure of the pressure-maintaining step (2) is 1.1 MPa, the rest is the same as embodiment 1.

[0081] Example 6

[0082] The only difference between this embodiment and embodiment 1 is that, except for the pressure holding time in step (2) being 2.5 hours, the rest is the same as embodiment 1.

[0083] Example 7

[0084] The only difference between this embodiment and embodiment 1 is that, except for the pressure holding time in step (2) being 12.5 hours, the rest is the same as embodiment 1.

[0085] Example 8

[0086] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the pressureless sintering in step (4) is 900° C., the rest is the same as embodiment 1.

[0087] Example 9

[0088] The only difference between this embodiment and embodiment 1 is that, except for the holding temperature of the pressureless sintering in step (4) being 1050° C., the rest is the same as embodiment 1.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 1 is that, except that the mold in step (2) is a rubber mold, the rest is the same as Example 1.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a lithium cobalt oxide ceramic target, and the preparation method comprises the following steps:

[0093] (1) Add 2 parts of polyacrylic acid and 200 parts of water into a powder mixing barrel and mix for 2 hours in the first stage; then add 95 parts of lithium cobalt oxide powder and mix for 12 hours in the second stage; finally add 3 parts of polyvinyl alcohol solution as a solute and mix for 12 hours in the third stage to obtain lithium cobalt oxide slurry;

[0094] (2) spraying and granulating the lithium cobalt oxide slurry, and then sequentially performing dry pressing and cold isostatic pressing, wherein the cold isostatic pressing pressure is 300 MPa and the holding time is 50 min to obtain a lithium cobalt oxide green body;

[0095] (3) placing the lithium cobalt oxide green body into a lifting furnace for degreasing at a temperature of 550° C. for a degreasing time of 3 h to obtain a degreased lithium cobalt oxide green body;

[0096] (4) The degreased lithium cobalt oxide green body is placed in a pressureless sintering furnace for pressureless sintering. The pressureless sintering temperature is 980° C. and the pressureless sintering holding time is 3 h to obtain the lithium cobalt oxide ceramic target.

[0097] Test Method

[0098] The density of the lithium cobalt oxide ceramic target prepared in Example 1-Example 9 and Comparative Example 1-Comparative Example 2 was tested. The test method was: using AKD-220A density instrument produced by Yangzhou Aikered Instrument Co., Ltd. to test the density of the lithium cobalt oxide ceramic target. The test method was drainage method, and the test results were recorded in Table 1.

[0099] Table 1

[0100]

[0101]

[0102] The test results show that:

[0103] (1) It can be seen from Examples 1 to 9 and Comparative Examples 1 to 2 that the present invention adopts slip injection molding and normal pressure sintering processes. Through slip injection molding, the water absorption of the gypsum mold is utilized to prepare a lithium cobalt oxide ceramic target with regular shape, high density and large size. The normal pressure sintering is adopted to reduce the production process and reduce the production cost. The present invention has the advantages of simplicity, high efficiency, low cost, short molding cycle and easy mass production.

[0104] (2) It can be seen from Example 1 and Example 4-Example 5 that the density of the lithium cobalt oxide ceramic target prepared by the present invention is further improved by further regulating the holding pressure after slurry injection molding.

[0105] (3) It can be seen from Example 1 and Example 6-Example 7 that the density of the lithium cobalt oxide ceramic target prepared by the present invention is further improved by further regulating the holding time after slurry injection molding.

[0106] (4) It can be seen from Example 1 and Example 8-Example 9 that the density of the lithium cobalt oxide ceramic target prepared by the present invention is further improved by further regulating the temperature of atmospheric pressure sintering.

[0107] In summary, the present invention adopts slip injection molding and normal pressure sintering processes. Through slip injection molding, the water absorption of the gypsum mold is utilized to prepare a lithium cobalt oxide ceramic target with regular shape, high density and large size. Normal pressure sintering is adopted to reduce the production process and reduce the production cost. It has the advantages of simplicity, high efficiency, low cost, short molding cycle and easy mass production.

[0108] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium cobalt oxide ceramic target, characterized in that: The preparation method comprises the following steps: (1) mixing a binder, a dispersant, a solvent and lithium cobalt oxide to obtain a lithium cobalt oxide slurry; (2) sequentially performing degassing, slip casting and drying on the lithium cobalt oxide slurry to obtain a lithium cobalt oxide green body; (3) Degreasing and sintering the lithium cobalt oxide green body in sequence to obtain the lithium cobalt oxide ceramic target.

2. The preparation method according to claim 1, characterized in that: The binder in step (1) comprises polyvinyl alcohol; Preferably, the amount of the binder is 2wt% to 5wt% of the total amount of the binder, the dispersant and the lithium cobalt oxide; Preferably, the dispersant includes any one or a combination of at least two of polyacrylic acid, polyacrylamide, sodium hexametaphosphate or sodium acrylate; Preferably, the amount of the dispersant is 0.5wt% to 3wt% of the total amount of the binder, the dispersant and the lithium cobalt oxide; Preferably, the solvent comprises deionized water.

3. The preparation method according to claim 1 or 2, characterized in that: The mixing in step (1) includes three stages of mixing; Preferably, the one-stage mixing includes: a one-stage mixing of a solvent and a dispersant to obtain a one-stage mixed material; Preferably, the mixing time is 0.5h to 3h; Preferably, the two-stage mixing comprises: mixing the first-stage mixture and lithium cobalt oxide powder in two stages to obtain a second-stage mixture; Preferably, the second-stage mixing time is 12h to 24h; Preferably, the three-stage mixing includes: mixing the second-stage mixture and the binder in three stages to obtain a mixed lithium cobalt oxide slurry; Preferably, the three-stage mixing time is 12 hours to 24 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The degassing in step (2) includes vacuum degassing; Preferably, the vacuum degree of the vacuum degassing is -0.98Mpa to -0.90Mpa; Preferably, after the vacuum degassing and before the grouting molding, the degassing pot is filled with gas for pressurization; Preferably, the pressurized pressure is 0.1 MPa to 1 MPa.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The size of the gypsum mold for grouting molding in step (2) is length (40cm-60cm)×width (70cm-90cm)×thickness (10cm-30cm); Preferably, after the grouting molding and before drying, pressure maintenance is performed; Preferably, the pressure of the pressure maintenance is 0.1MPa to 1MPa; Preferably, the pressure maintaining time is 3h to 12h.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The drying temperature in step (2) is 40° C. to 50° C. Preferably, the drying insulation time is 20h to 48h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The degreasing holding temperature in step (3) is 500° C. to 600° C.; Preferably, the degreasing insulation time is 1 h to 5 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The holding temperature of the pressureless sintering in step (3) is 950° C. to 1000° C.; Preferably, the holding time of the atmospheric pressure sintering is 1 h to 5 h.

9. A lithium cobalt oxide ceramic target, characterized in that: The lithium cobalt oxide ceramic target is prepared by the preparation method described in any one of claims 1 to 8.

10. An application of the lithium cobalt oxide ceramic target material as claimed in claim 9, characterized in that: The lithium cobalt oxide target is used for the positive electrode of a solid-state thin-film battery.

Citation Information

Patent Citations

  • Lithium cobalt oxide target material and preparation method thereof

    CN102181840A

  • Preparation method of slip-casting type rotary ceramic target

    CN103833375A

  • Preparation method of lithium cobaltate target

    CN106048542A

  • Method for preparing oxide ceramic target material green body

    CN108046767A

  • Deposition of licoo2

    JP2008523567A